Perceptions about the teaching of mathematics mediated with TDIC - Pires de Souza , Wedla; de Oliveira Cândido Gonçalves, Viviane (Seven Editora, 2023)
The study of this article aims to discuss the perceptions and Freirean contributions in the teaching of Mathematics allied to the use of TDIC. This study proposes as a generating question, the following question: how can we associate the TDIC and Freirean contributions to the teaching process to provide a learning of Mathematics in a more dynamic and attractive way contextualized with the reality of the students? With the purpose of presenting some Freirean perceptions in the teaching of Mathematics regarding the use of TDIC in Mathematics classes. The methodology used in this work was the qualitative bibliographic research supported by Freirean perceptions.  The theoretical framework had its main basis the work "Pedagogy of Autonomy" by Freire (1996), supported by other theoretical studies by Amancio (2020), Brasil (2017), D' Ambrósio (1996), Lemos (2018), Schmitt (2018), Silva (2018), among others. With this study we verified the need to insert new pedagogical educational practices with the TDIC to promote different possibilities for the student to build their own knowledge of Mathematics with the use of the TDIC.  Moreover, we understand that Freirean perceptions establish a relationship between the use of digital technologies and the teaching of Mathematics in various aspects of Freirean ideas, especially when Freire (1996) reports that the teacher should not transfer knowledge, but produce new possibilities to build and develop the same. With this, we realize that the use of TDIC can offer a new construction in the process of teaching and learning Mathematics in the formation of students more critical, active, dynamic and prepared for the impactful changes that occur in society. DOI: https://doi.org/10.56238/Connexpemultidisdevolpfut-083